Spiritualitas Seorang Guru - Yusron Yusuf (MODELING: Jurnal Program Studi PGMI, 2017)
Education in the era of globalization, modernization and development of the times gets serious enough challenge. Therefore, the need for change and improvement in the attitude of learning in school to achieve the goal of better education. Changes and improvements in learning attitude including through the spirituality of a teacher. So the heart of a teacher in the learning process will feel calm, relax, blessing, useful, and takes pride in carrying out duties as a teacher.In the process of learning, the teacher has the role and duties as a source of material that never dry in managing the learning process. The learning activities are expected to be greeted joyously by students. So that the learning process is quiet, relax, blessing, benefits, and are proud to be a teacher. To create such a learning atmosphere of a teacher is not enough just to rely on the intelligence in the field of science, but it is indispensable soul of a teacher who covers: 1) gives the best example, 2) time management, 3) treat students with respect and compassion, 4) be aware of the emotions of teachers, 5) a figure forgiving, 6) Iqra (read), 7) put their trust.